THE INFLUENCE OF POPULATION ADMINISTRATIVE SERVICE QUALITY ON PUBLIC SATISFACTION IN SARUNI KELURAHAN OFFICE, DISTRICT MAJASARI, PANDEGLANG DISTRICT - Firgita Fadillah (NIAGARA Scientific Journal, 2023)
The purpose of this study was to determine the effect of population service quality on community satisfaction in the Saruni sub-district office. The problems that exist are, service officers in charge of serving population administration are not in place when they are on duty, there are still services that have not been in accordance with the set target time, and there is no clear service rate and officers are easily angry and offended. The research method used in this research is Survey Research method using a quantitative approach. The variable quality of population administration services at the Saruni Village Office, Majasari District, Pandeglang Regency is good, it can be assessed that the average interpretation result is 3.01 including good criteria, while the community satisfaction variable gets an average interpretation result of 2.67 also includes good criteria. The results of hypothesis testing obtained t arithmetic results of 16.819, greater than t table 0.202 with an error rate of 5%, it means that Ha is accepted and Ho is rejected. The results of the determination test of the effect of the quality of population administration services on community satisfaction obtained a figure of 62.41% while the remaining 37.59% was influenced by other factors that the authors did not examine.